2018
DOI: 10.1038/s41467-018-07702-z
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli can survive stress by noisy growth modulation

Abstract: Gene expression can be noisy, as can the growth of single cells. Such cell-to-cell variation has been implicated in survival strategies for bacterial populations. However, it remains unclear how single cells couple gene expression with growth to implement these strategies. Here, we show how noisy expression of a key stress-response regulator, RpoS, allows E. coli to modulate its growth dynamics to survive future adverse environments. We reveal a dynamic positive feedback loop between RpoS and growth rate that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 66 publications
7
97
1
Order By: Relevance
“…This observation is in line with the prediction of Sigma38 playing an important role in shaping genome-wide expression noise, as ppGpp is an 'alarmone' responsible for regulating genes upon entry into stationary phase Hauryliuk et al , 2015 and promoters regulated by Sigma38 require ppGpp for induction Kvint et al , 2000. Moreover, it was recently shown that rpoS activity is heterogeneous among single cells in M9 glucose Patange et al , 2018. Two further significant noise propagators are CRP and PhoB. CRP is a global regulator of genes involved in carbon source catabolism and its activity has been proposed to reflect carbon source influx You et al , 2013.…”
Section: Noise Propagation Explains the Condition-dependent Noise Levsupporting
confidence: 88%
“…This observation is in line with the prediction of Sigma38 playing an important role in shaping genome-wide expression noise, as ppGpp is an 'alarmone' responsible for regulating genes upon entry into stationary phase Hauryliuk et al , 2015 and promoters regulated by Sigma38 require ppGpp for induction Kvint et al , 2000. Moreover, it was recently shown that rpoS activity is heterogeneous among single cells in M9 glucose Patange et al , 2018. Two further significant noise propagators are CRP and PhoB. CRP is a global regulator of genes involved in carbon source catabolism and its activity has been proposed to reflect carbon source influx You et al , 2013.…”
Section: Noise Propagation Explains the Condition-dependent Noise Levsupporting
confidence: 88%
“…The network was trained on images from three different multi-position time-lapse movies acquired in our lab, and on movies available from the literature [11,16,17,28,29]; we then evaluated on a third data set acquired in our lab weeks later as well as on data from the literature ( Table 1). To demonstrate generalizability of the approach, and to evaluate performance against other analysis software, we also used the time-lapse image datasets provided with the mother machine analysis software tools Molyso [11], MoMA [16], and BACMMAN [17] to evaluate the performance of DeLTA on completely new data by performing "leave-one-out" training and evaluation pairings.…”
Section: Segmentationmentioning
confidence: 99%
“…In this scenario heterogeneity is no more than an interesting artefact of the regulatory system. The alternative is that heterogeneity is beneficial, perhaps in a bet-hedging sense, as has been indicated before in bacterial stress response systems ( Carey et al, 2018; Patange et al, 2018 ). Actually testing for evidence of bet-hedging is generally challenging ( Simons, 2011; Grimbergen et al, 2015 ), and the strength as a strategy depends both on the specifics of the stress response system and on the typical frequency of environmental changes ( Kussell and Liebler, 2005 ).…”
Section: Discussionmentioning
confidence: 91%